The South Green Portal: a comprehensive resource for tropical and Mediterranean crop genomics - South Green collaborators (Elsevier, 2016)
The South Green Web portal (http://www.southgreen.fr/) provides access to a large panel of public databases, analytical workflows and bioinformatics resources dedicated to the genomics of tropical and Mediterranean crops. The portal contains currently about 20 information systems and tools and targets a broad range of crops such as Banana, Cacao, Cassava, Coconut, Coffee, Grape, Rice and Sugarcane.